UZBEK NATIONAL FOLK EPIC (BASED ON "ALPAMYSH") - Tosheva Dilbar Muzaffar kizi; Tosheva Sabrina Muzaffar kizi (Academia Science Repository, 2023)
In the article, during the reading of the epic, the traditions of our people, which have been studied and polished year by year, how their social relations were in ancient times, "Alpamysh" is not only a unique epic of centuries-old folk art with great ideas, but also a national it is expressed that it is an encyclopedia of values, and at the same time it has taken an important place in the literature of other countries.